THE PORTRAYAL OF BULLYING IN FILM THE FAT BOY CHRONICLES (PSYCHOLOGICAL APPROACH) - Nabar, Agnesia D; Liru, Marianus W; Doi, Maksimilianus (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2024)
The aims of this study were to determine the types of bullying experienced by the main character and would find out the impact on the mental health of the main character as a result of this bullying behavior in the film The Fat Boy Chronicles. The research method used in this study was a qualitative descriptive method. This study used bullying theory by Alen and Freud to analyze the data, and a psychological approach was also used in this study. The writer used the library method to find the theory and data needed for this thesis. The primary data consist from the film The Fat Boy Chronicles. Secondary data consist from books, articles, journals, dictionaries and theses The results of this study answer two problems of the study. First, the writer can find out the types of bullying experienced by the main character in the film. There are three typesof bullying that the writer found in this film, namely physical bullying, verbal bullying and emotional bullying. Second, the writer is able to find out the impact that occurred on mental health, namely anxiety and depression, self-esteem and self-identity, isolation.